2021
DOI: 10.23887/jere.v5i1.31643
|View full text |Cite
|
Sign up to set email alerts
|

Physics Teachers’ Perspectives on The Availability of The Integration of E-Formative Assessment in E-Learning based on Website (EFA in ELboW) during Covid-19 Pandemic

Abstract: In the field of education, the COVID-19 demands changes in the learning process. It is important to know the changes that have occurred so that we can take some actions to face the changes that occurred, and help teachers prepare for the changes that occur in the learning process, especially in the physics learning process. This study aims to determine changes in the teaching, assessing, and using validated instrument aspect due to the COVID-19 pandemic. Also, gathered teacher perspectives on the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
2
4
0
1
Order By: Relevance
“…Related to the first research question, our finding about teachers not experiencing challenges with using technology is in agreement with the study from Lemay et al ( 2020 ) but findings related to lacking technological skills are not supported (O’Brien 2021 ; Trust and Whalen 2021 ). The challenges in interaction is supported by previous research (Dew et al 2021 ; Romadhon et al 2021 ; Trust and Whalen 2021 ). Partially conflicting findings related to interaction from Kannan et al ( 2020 ) and Lemay et al ( 2020 ) might be explained with different ways of instruction and data gathering methods.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Related to the first research question, our finding about teachers not experiencing challenges with using technology is in agreement with the study from Lemay et al ( 2020 ) but findings related to lacking technological skills are not supported (O’Brien 2021 ; Trust and Whalen 2021 ). The challenges in interaction is supported by previous research (Dew et al 2021 ; Romadhon et al 2021 ; Trust and Whalen 2021 ). Partially conflicting findings related to interaction from Kannan et al ( 2020 ) and Lemay et al ( 2020 ) might be explained with different ways of instruction and data gathering methods.…”
Section: Discussionsupporting
confidence: 57%
“…(Lemay et al 2020 ) This finding is supported by Kannan et al ( 2020 ) who have reported a better engagement over internet whilst a specially designed intervention for remote teaching has been utilised. Then again, the sense of community and the number of discussions has declined in remote teaching (Dew et al 2021 ; Romadhon et al 2021 ; Trust and Whalen 2021 ). O’Brien ( 2021 ) points out that whilst interacting with students online, one should keep the resources and equality of students in mind.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…E-formative assessment yang diintegrasikan dalam pembelajaran dapat meningkatkan penguasaan konsep siswa dengan kategori pengaruh kuat (S. Kusairi et al, 2021). E-formative assessment meningkatkan intensitas interaksi antara guru dengan siswa yang merupakan dukungan belajar yang menjadikan belajar lebih efisien (Köse, 2010;Romadhon et al, 2021). Dengan memaksimalkan waktu pembelajaran seperti ini, maka dapat memaksimalkan penguasaan konsep siswa (Bazelais & Doleck, 2018).…”
unclassified